2021
DOI: 10.3329/ijarit.v10i2.51576
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the risk and resilience of flash flood in Sunamgonj haor region of Bangladesh

Abstract: Bangladesh faces various types of natural hazards from its birth due to geographical location and physiographic conditions. Flood is the most common event among them. Northeastern part of Bangladesh faces flash flood almost every year with large scale of damage. Tanguar haor, (a famous Ramsar site of Bangladesh) located in Tahirpur upazila of Sunamgonj district. This wetland adjacent area is the most vulnerable zone in terms of flash flood hazard. About more than 80%, people are the direct victim of this hazar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…This perhaps implies that the needy people suffer the hardest time during floods due to inadequate means of protection measures and also the loss of property and income (Parvin et al 2016). Another study by Islam et al (2020) evaluates the risk and resilience level of flash floods and reported that 55% of people of Tahirpur in Tanguar haor have low resilience that renders them more vulnerable. So, the higher the number of floods, the higher the vulnerability and impacts caused by the hazards will be higher also.…”
Section: Comparison Of Water Level Flow and Extent Over The Period 2019-2015mentioning
confidence: 99%
“…This perhaps implies that the needy people suffer the hardest time during floods due to inadequate means of protection measures and also the loss of property and income (Parvin et al 2016). Another study by Islam et al (2020) evaluates the risk and resilience level of flash floods and reported that 55% of people of Tahirpur in Tanguar haor have low resilience that renders them more vulnerable. So, the higher the number of floods, the higher the vulnerability and impacts caused by the hazards will be higher also.…”
Section: Comparison Of Water Level Flow and Extent Over The Period 2019-2015mentioning
confidence: 99%